The Knowledge Economy, Gender and Stratified Migrations - Eleonore Kofman (Studies in Social Justice, 2007)
The promotion of knowledge economies and societies, equated with the mobile subject as bearer of technological, managerial and cosmopolitan competences, on the one hand, and insecurities about social order and national identities, on the other, have in the past few years led to increasing polarisation between skilled migrants and those deemed to lack useful skills. The former are considered to be bearers of human capital and have the capacity to assimilate seamlessly and are therefore worthy of citizenship; the latter are likely to pose problems of assimilation and dependency due to their economic and cultural ‘otherness’ and offered a transient status and partial citizenship by receiving states. In the European context this trend has been reinforced by the redrawing of European geopolitical space creating new boundaries of exclusion and social justice. The emphasis on the knowledge economy also generates gender inequalities and stratifications based on skills and types of knowledge with implications for citizenship and social justice.